Using Charades Games in Enhancing Eight Grade Students’ Speaking Skills - Nurhidayah, Putri; Risnawati, Risnawati; Febriani, Hanura (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The purpose of this study was to see the effect of the charades game method in improving the speaking skills of eighth grade students at PKKPS Wustha Hidayatul Qomariyah Bengkulu City. This type of research is experimental research with Quasi Experimental design. The population in this study were all eighth grade students at PKKPS Wustha Hidayatul Qomariyah as many as 67 students. While the sample used was only 30 students, namely students of class VIII A and VIII B female with the sampling technique used was purposive sampling, the instrument used in this study was a test instrument to test students' speaking ability. Then based on the calculation of the Independent Sample t Test, the value (sig) = 0.29> 0.05 is obtained so it can be concluded that there is an effect of the charades game method in improving the speaking skills of eighth grade students at PKKPS Wustha Hidayatul Qomariyah Bengkulu City.